The relationship between alcohol consumption and erectile dysfunction in men: a systematic review - Roghayeh Abdnezhad; Mahtab Sattari; Fatemeh Jalali-Chimeh; Hedyeh Riazi; Zohreh Keshavarz (Mashhad University of Medical Sciences, 2024)
Introduction: Erectile dysfunction is one of the most common sexual health problems in men and is defined by the persistent inability to achieve or maintain an erection for sexual performance. Several risk factors have been mentioned regarding its occurrence. Alcohol is a central nervous system depressant that can lead to erectile dysfunction. The present study was conducted with the aim of a systematic review of the studies conducted on the relationship between erectile dysfunction and alcohol consumption. Methods: The present study was conducted by searching in reliable databases of Web of Science, PubMed, Scopus and Google Scholar search engine without time limit until 2024 by two independent researchers and using Mesh keywords including: Dysfunction, Erectile, Alcohol Drinking, Alcoholism, and Male Sexual Impotence. To evaluate the quality of the articles, the Newcastle-Ottawa scale was used for observational studies or the Cochrane risk of bias tool for interventional studies. Results: After reviewing and evaluating the quality of 196 selected articles, finally 15 articles were included in the systematic review. The results of most studies show that alcohol consumption is effective in the occurrence of erectile dysfunction in men. The duration, frequency and amount of alcohol consumption were also effective on the severity and occurrence of erectile dysfunction. It has also been shown that avoiding alcohol can be effective in improving penile erection. Conclusion: Despite the contradictory results of some studies, the findings of most studies show the existence of a relationship between alcohol consumption and erectile dysfunction.